An Aging Workforce: Employment Opportunities and Obstacles - Full Professor, Institute of Economic Sciences (Cadmus, 2013)
The last decade has witnessed significant changes in the structure of unemployment in the global labour market. This is corroborated by the fact that the global workforce is rapidly aging and the share of people aged 50 and over in the structure of the labour market is increasing. In line with this trend, unemployment issues should be considered as a global problem that cannot be fully resolved at the level of any individual country separately.The main objective of this paper is to throw some light on the aging workforce and the elderly population’s opportunity to realise their right to work and be treated equally with younger age groups. Hence, the paper simultaneously focuses on the age and gender discrimination of elderly population in terms of their employment prospects. The aim of our research is not only to point out certain stereotypes concerning the elderly labour force, but also to stress that unless preconditions for overcoming these stereotypes are created and employment opportunities are given to this segment of the labour force, full employment as an ultimate goal of global economic policy cannot be achieved. It is in accordance with these considerations that we offer a model to achieve this goal.